The Tension in the Great Lakes Region Over the M23 Rebellion in Eastern Democratic Republic of CONGO (DRC) - Lukuba Machibya; Zora Sukabdi (International Journal Labs, 2025)
The re-emergence of the March 23 Movement (M23) in Eastern Democratic Republic of Congo (DRC) has reignited tensions in the Great Lakes Region, exposing deep-rooted historical, ethnic, political, and economic grievances. This study analyzes the causes, dynamics, and consequences of the rebellion, situating it within the colonial legacy, state fragility, and regional competition, with particular emphasis on the roles of Rwanda and Uganda. Using Conflict Theory and Realist International Relations Theory, the research highlights key drivers of conflict, including the socio-political marginalization of the Congolese Tutsi minority, competition over vast natural resources, and the weakness of the Congolese state. Qualitative methods and secondary data from UN, AU, and NGO reports form the basis of this analysis. Findings reveal that the rebellion persists due to unfulfilled peace agreements, ethnic divisions, and the shadow economy fueled by illicit resource extraction. The consequences are severe: over a million displaced people, widespread human rights abuses, and devastated livelihoods. Despite interventions by the East African Community, MONUSCO, and international sanctions, mistrust, weak institutions, and conflicting regional interests hinder peace. The study concludes that only a holistic peacebuilding process—encompassing regional cooperation, accountability for war crimes, governance reforms, and inclusive economic growth—can break the cycle of violence and foster stability in Eastern DRC and the wider Great Lakes Region.